Expert Consensus on the Diagnosis and Treatment of NRG1/2 Gene Fusion Solid Tumors - Xu, Chunwei; Wang, Qian; Wang, Dong; Wang, Wenxian; Fang, Wenfeng; Li, Ziming; Liu, Aijun; Yu, Jinpu; Zhong, Wenzhao; Wang, Zhijie; Zhang, Yongchang; Liu, Jingjing; Zhang, Shirong; Cai, Xiuyu; Liu, Anwen; Li, Wen; Zhan, Ping; Liu, Hongbing; Lv, Tangfeng; Miao, Liyun; Min, Lingfeng; Chen, Yu; Yuan, Jingping; Wang, Feng; Jiang, Zhansheng; Lin, Gen; Huang, Long; Pu, Xingxiang; Lin, Rongbo; Liu, Weifeng; Rao, Chuangzhou; Lv, Dongqing; Yu, Zongyang; Li, Xiaoyan; Tang, Chuanhao; Zhou, Chengzhi; Zhang, Junping; Xue, Junli; Guo, Hui; Chu, Qian; Meng, Rui; Wu, Jingxun; Zhang, Rui; Zhou, Jin; Zhu, Zhengfei; Li, Yongheng; Qiu, Hong; Xia, Fan; Lu, Yuanyuan; Chen, Xiaofeng; Ge, Rui; Dai, Enyong; Han, Yu; Pan, Weiwei; Pang, Fei; He, Qingqing; Huang, Jintao; Wang, Kai; Wu, Fan; Xu, Bingwei; Wang, Liping; Zhu, Youcai; Lin, Li; Xie, Yanru; Lin, Xinqing; Cai, Jing; Xu, Ling; Li, Jisheng; Jiao, Xiaodong; Li, Kainan; Wei, Jia; Feng, Huijing; Wang, Lin; Du, Yingying; Yao, Wang; Shi, Xuefei; Niu, Xiaomin; Yuan, Dongmei; Yao, Yanwen; Huang, Jianhui; Feng, Yue; Zhang, Yinbin; Sun, Pingli; Wang, Hong; Ye, Mingxiang; Wang, Zhaofeng; Hao, Yue; Wang, Zhen; Wan, Bin; Lv, Donglai; Yang, Shengjie; Kang, Jin; Zhang, Jiatao; Zhang, Chao; Ou, Juanjuan; Shi, Lin; Wang, Yina; Li, Bihui; Zhang, Zhang; Li, Zhongwu; Liu, Zhefeng; Yang, Nong; Wu, Lin; Wang, Huijuan; Jin, Gu; Wang, Guansong; Wang, Jiandong; Fang, Meiyu; Fang, Yong; Li, Yuan; Wang, Xiaojia; Zhang, Yiping; Zhu, Xixu; Shen, Yi; Ma, Shenglin; Wang, Biyun; Si, Lu; Song, Yong; Lu, Yuanzhi; Chen, Jing; Song, Zhengbo (Global Medical Genetics, 2024)
The fusion genes NRG1 and NRG2, members of the epidermal growth factor (EGF) receptor family, have emerged as key drivers in cancer. Upon fusion, NRG1 retains its EGF-like active domain, binds to the ERBB ligand family, and triggers intracellular signaling cascades, promoting uncontrolled cell proliferation. The incidence of NRG1 gene fusion varies across cancer types, with lung cancer being the most prevalent at 0.19 to 0.27%. CD74 and SLC3A2 are the most frequently observed fusion partners. RNA-based next-generation sequencing is the primary method for detecting NRG1 and NRG2 gene fusions, whereas pERBB3 immunohistochemistry can serve as a rapid prescreening tool for identifying NRG1-positive patients. Currently, there are no approved targeted drugs for NRG1 and NRG2. Common treatment approaches involve pan-ERBB inhibitors, small molecule inhibitors targeting ERBB2 or ERBB3, and monoclonal antibodies. Given the current landscape of NRG1 and NRG2 in solid tumors, a consensus among diagnostic and treatment experts is proposed, and clinical trials hold promise for benefiting more patients with NRG1 and NRG2 gene fusion solid tumors.
Keywords: tyrosine receptor kinase; monoclonal antibodies; precision medicine; targeted therapy; solid tumor; fusion